Best Principles for Criminal Assets Management: Conceptual Framework (Global Business Management Review (GBMR), 2022)
This paper follows a normative research methodology of law, and will make collaboration with economic approach to build a proper concept for good criminal assets management, and good management principle implementation in order to regain the revenue of state financial losses through a dialogue between law and economic approaches. As it understood, transnational crime is one of the most vital crimes involving any kind of money and property as proceeds of crime. It is adapting things to fit their illegal activities. Corruption and Money Laundering as transnational crime are like two faces of coin. Pursuing proceeds of crime is the effective method in order to cut the crimes. To cut corruption, it can use anti money laundering mechanism. The problem of asset forfeiture is not as simply as designed in the theory. The existence of criminal punishment and forfeiture regime could be very problematic. When criminal assets should be forfeited, the domestic law meets difficulties especially when forfeited assets are in foreignjurisdiction. Thus it needs any proper and right mechanism of asset recovery and asset management in order to recover state financials loss. Maintaining the asset require special institution, good management and cooperation principles to implement it.